Grassroots Election Oversight: Enhancing Electoral Accountability and Civic Engagement - Nur Hamidin, Bambang; Hendy Setiawan (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2025)
Despite high expectations for Indonesia’s elections, including the most recent in 2024, widespread violations undermined their integrity. In response, there is a pressing need for grassroots participation in electoral monitoring to complement formal oversight by government bodies. This article investigates community-based participatory election supervision through the establishment of Election Monitoring Villages in Batang Regency, Indonesia. The study aims to assess how these initiatives enhance grassroots democratic literacy and foster meaningful political engagement. Employing a descriptive qualitative approach, data were collected through interviews with 10 informants, field observations, and a review of relevant literature. Four monitoring villages—Sijono, Bandar, Ujung Negoro, and Sidorejo—were established by the local Elections Supervisory Agency (Bawaslu) based on strategic and participatory considerations. The findings reveal that these villages have raised public awareness of electoral processes, strengthened civic responsibility, and encouraged residents to actively report violations. Academically, this study contributes to the discourse on participatory democracy by offering empirical evidence of how structured village-based programs can cultivate political awareness and expand community oversight. The research concludes that monitoring villages function not only as mechanisms for electoral supervision but also as platforms for civic education and democratic consolidation. Meskipun pemilu di Indonesia, termasuk yang paling mutakhir pada tahun 2024, diharapkan menjadi tonggak kedewasaan demokrasi, berbagai pelanggaran yang meluas justru merusak integritasnya. Menyikapi hal tersebut, muncul kebutuhan mendesak akan partisipasi masyarakat dalam pengawasan pemilu di tingkat akar rumput guna melengkapi pengawasan formal yang dilakukan lembaga pemerintah. Artikel ini meneliti pengawasan pemilu partisipatif berbasis komunitas melalui pembentukan desa pengawasan di Kabupaten Batang, Indonesia. Penelitian ini bertujuan untuk menilai bagaimana inisiatif tersebut meningkatkan literasi demokrasi masyarakat dan mendorong keterlibatan politik yang lebih bermakna. Dengan menggunakan pendekatan kualitatif deskriptif, data dikumpulkan melalui wawancara dengan 10 informan, observasi lapangan, serta telaah literatur yang relevan. Empat Desa Pengawasan Pemilu—Sijono, Bandar, Ujung Negoro, dan Sidorejo—dibentuk oleh Badan Pengawas Pemilu (Bawaslu) setempat berdasarkan pertimbangan strategis dan partisipatif. Temuan penelitian menunjukkan bahwa desa-desa ini telah meningkatkan kesadaran publik terhadap proses pemilu, memperkuat tanggung jawab kewargaan, serta mendorong masyarakat untuk secara aktif melaporkan pelanggaran. Secara akademis, penelitian ini memberikan kontribusi pada wacana demokrasi partisipatif dengan menghadirkan bukti empiris mengenai bagaimana program berbasis desa yang terstruktur dapat menumbuhkan kesadaran politik dan memperluas pengawasan masyarakat. Penelitian ini menyimpulkan bahwa desa pengawasan berfungsi tidak hanya sebagai mekanisme pengawasan pemilu, tetapi juga sebagai wadah pendidikan kewargaan dan konsolidasi demokrasi.